Are Boys Really Better Than Girls at History? A Critical Examination of Gender-related Attainment Differentials Within the English Educational System. Issue 2 (1st October 2009) - Hodkinson, Alan
Abstract : The paper examines research which contends that gender differentials exist of primary history which postulates that males are more able to assimilate historical concepts than their female counterparts. A review of the literature denotes that previous studies are based upon small samples, are subject to methodological delimitation and produce contradictory results. The paper contends, therefore, that these limitations must article examines, through classroom based research, whether gender-related performance differentials exist within the teaching and learning of history for children aged eight to sensory assessments and unfocussed observations. Based upon statistical analysis of the study's results it is concluded that gender does not act as a performance determinant in the teaching and learning of primary history.